Respostas
respondido por:
2
Temos então:
A(1,7)
B(11,3)
Calculando a distância entre dois pontos:
D=√(x2-x1)²+(y2-y1)²
D=√(11-1)²+(3-7)²
D=√(10)²+(-4)²
D=√100+16
D=√116
A(1,7)
B(11,3)
Calculando a distância entre dois pontos:
D=√(x2-x1)²+(y2-y1)²
D=√(11-1)²+(3-7)²
D=√(10)²+(-4)²
D=√100+16
D=√116
laizedeusefiel:
valeu mesmooo
respondido por:
0
D = V(x2-x1)^2 + (y2-y1)^2
D = V(11-1)^2 + (3-7)^2
D = V100+16
D = V116 ==> V2^2.29
D = 2V29
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás